Language attitudes towards hokkien and mandarin among students in Universiti Malaysia Sarawak (UNIMAS) - Puah, Yann Yann (Universiti Malaysia Sarawak (UNIMAS), 2009)
It was reported that half of the world languages were dying due to language shift and language death. It was estimated that approximately six hundred languages would still be used by the year 2010. Hokkien, as a vernacular language in Malaysia, had showed symptoms of language shift. Thus, this study was carried out to examine the language attitudes towards Mandarin and Hokkien. It was conducted among the students in Universiti Malaysia Sarawak (UNIMAS). The two objectives of this study were to uncover these students’ attitudes towards the two languages, the speakers of these two languages as well as the level of pride of the participants towards their own Hokkien identity. This study had used a combination of qualitative and quantitative methods which were matched-guise technique, questionnaire and interview. A total of 50 participants took part in this study with 25 males and 25 females. All of them were involved in matched-guise technique and questionnaire but only ten participants with strong Hokkien identity were interviewed. The statistical analysis from matched-guise technique showed that these participants had conformed to the expected situation where Mandarin, a standard language, was ranked higher than Hokkien, a vernacular language. The same results were found when analysis of questionnaires and interviews were conducted, that is, Hokkien was ranked socially lower because the domains it covered were restricted. In contrast, Mandarin was perceived as a language that was widely used in both formal and informal situations. Thus, the assumption of such results in the findings was due to the increasing used of Mandarin in Malaysia society. Even though a majority of the participants self-reported that they were proud of their own Hokkien identity, language shift was seen in the participants’ attitudes towards the language where Mandarin was slowly taking over the role of Hokkien.